Combining fault location estimates for a multi-tapped distribution line - Jahanger, H.K.; Sumner, Mark; Thomas, David W.P. (2017)
Multi-tapped lines are common in integrated power systems and microgrids which supply variable loads between the main source and the main load. Adopting a cost effective and efficient method for fault location is important for fast power recovery and improving system reliability. A method requiring measurements only at the ends of the main distribution line is proposed in this paper to solve the issue of locating faults on the tapped lines as well as on the main line without any measurement required from the taps. A combination of single-ended and double-ended algorithms based on higher frequency impedance estimation are utilized to locate the faults within the tapped line. The study considers different fault types in different locations as well as various fault inception angles. The presented results shows the efficiency and the accuracy of the suggested technique with maximum error less than 3% of the total line length.